2005
DOI: 10.1002/cta.317
|View full text |Cite
|
Sign up to set email alerts
|

Another FIR lattice structure

Abstract: SUMMARYA new two multiplier FIR lattice structure is derived by using the digital two-pair concept, which produces two transfer functions H i (z) and H i (z) having the complementary relationship) satisÿed in the conventional FIR lattice structure. The new structure should be useful in crossover networks as well as in multirate signal processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Such a pair of complementary transfer functions is useful in crossover networks as well as in multi-rate signal processing. Following the same two-pair approach, it was found that the required t parameters are given by (Dutta Roy & Vishwanath 2005)…”
Section: Derivation Of Another Latticementioning
confidence: 99%
“…Such a pair of complementary transfer functions is useful in crossover networks as well as in multi-rate signal processing. Following the same two-pair approach, it was found that the required t parameters are given by (Dutta Roy & Vishwanath 2005)…”
Section: Derivation Of Another Latticementioning
confidence: 99%
“…Filter banks are often realized as FIR or Chebyshev filters. However, in this case an extremely high filter order is necessary [6][7][8][9]. The transfer functions in the formulae (1) are written in the form of rational functions under the assumption that the order n of the filter is an odd number.…”
Section: H L (S) =mentioning
confidence: 99%
“…In a subsequent paper [5], this question was answered in the affirmative by deriving a new lattice structure for satisfying the relationship Equation (8) implies that Hj(z) and Gj(z) are complementary filters, i.e. if H,(z) is low-pass, then G;(z) is high-pass and vice versa.…”
Section: Introductionmentioning
confidence: 96%
“…The present paper is a generalization of [5], in which HJz) and GJz) are two arbitrary transfer functions, given by 13 (1) Note that HN(z) and GN(z) have the same magnitude but equal and opposite phase on Iz I= 1. Hence for designing a single digital filter with prescribed magnitude specifications, it is wasteful in multipliers, requiring double the number as compared to canonic realization.…”
Section: Introductionmentioning
confidence: 99%